2017
DOI: 10.18553/jmcp.2017.23.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medicaid Policy Changes on Medication Adherence: Differences by Baseline Adherence

Abstract: This study was partly funded by a grant from the Robert Wood Johnson Foundation for use in data creation. Maciejewski was supported by a Research Career Scientist Award from the Department of Veterans Affairs (RCS 10-391) and owns stock in Amgen. Farley reports consultancy fees from Daiichi Sankyo outside of the conduct of this study. The other authors report no financial or other conflicts of interest related to the subject of this article. The views expressed in this article are those of the authors and do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…The insti- is considered to more accurately measure adherence than other methods. [14][15][16][17] From the supply diary, we calculated long-term adherence using the proportion of days covered (PDC) measure by dividing the number of days with medication available by the number of days during the 365-day follow-up period (days 1-365). 18 We also calculated adherence in days 31-365 and days 121-365 after the index date as "delayed" adherence outcome assessment periods for secondary analyses.…”
Section: ■■ Methods Data Source and Patient Populationmentioning
confidence: 99%
“…The insti- is considered to more accurately measure adherence than other methods. [14][15][16][17] From the supply diary, we calculated long-term adherence using the proportion of days covered (PDC) measure by dividing the number of days with medication available by the number of days during the 365-day follow-up period (days 1-365). 18 We also calculated adherence in days 31-365 and days 121-365 after the index date as "delayed" adherence outcome assessment periods for secondary analyses.…”
Section: ■■ Methods Data Source and Patient Populationmentioning
confidence: 99%
“…It has been reported that patients in Finland and Sweden were more likely to be non‐adherent for CVD prevention therapy after retirement . Amin et al found a decline in adherence for lipid‐lowering drug and antihypertensive cohorts after North Carolina Medicaid policy changes . Wang et al assessed medication adherence changes after a co‐payment increase for patients who had diabetes, hypertension or both conditions, and found patients with lower comorbidity were more sensitive to co‐payment increase than higher comorbidity patients .…”
Section: Introductionmentioning
confidence: 99%
“…This approach of using a uniform denominator of 365 days is a traditional way that has been used by other researchers for assessing medication adherence. [32][33][34] For this analysis, we also adjusted the days supply using drug claims from January to March 2013 in order to account for diabetes drug fills made before the beginning of the preperiod (i.e., April 1, 2013). Any overlapping days supply was adjusted using the same approach as in the primary analysis.…”
Section: Discussionmentioning
confidence: 99%